Surrogate modeling and optimization of the leaching process in a rare earth elements recovery plant - Fardis, Dimitrios M.; Oh, Donghyun; Sahinidis, Nikolaos V.; Garciadiego, Alejandro; Lee, Andrew (Computers & chemical engineering, 2025)
Critical minerals (CMs) and Rare Earth Elements (REEs) play a vital role in crucial infrastructure technologies such as renewable energy generation and batteries. Recovering them from waste materials has recently been found to significantly reduce environmental impact and supply chain costs related to these materials. In this work, we investigate surrogate modeling techniques aimed to simplify the modeling, simulation, and optimization of the leaching processes involved in CM and REE recovery flowsheets. As there is currently a lack of systematic studies on this topic, we perform extensive computational testing to ascertain which surrogate models are easier to construct and offer high predictive accuracy. Our results suggest that sparse quadratic models balance predictive accuracy and computational efficiency. Training and using these surrogates for global optimization of the leaching process requires two orders of magnitude fewer measurements and is up to four orders of magnitude faster than optimizing the original simulation using equation-oriented optimization or derivative-free optimization. •Which surrogate modeling techniques are accurate for critical mineral processes?•Can we build accurate surrogate models of critical processes with few measurements?•Can we model and optimize critical mineral processes with simple surrogate models?